Methanol for Hydrogenation and Methylation of Carbonyls: Advances and Challenges in Homogeneous Catalysis - Padmor, Manohar Shivaji; Pratihar, Sanjay (Synlett, 2024)
The catalytic dehydrogenation of methanol to give formaldehyde or formic acid, followed transfer hydrogenation and/or tandem (de)hydrogenation for the hydrogenation and C-methylation of carbonyls, offers advantages over traditional methods, including milder reaction conditions, improved safety, greater selectivity, and enhanced sustainability. This account provides a comprehensive overview of homogeneous catalysts reported for the transfer hydrogenation and C-methylation of various substrates, including ketones, chalcones, esters, and amides, using methanol as both a hydrogen donor and methylation source. We provide specific examples and mechanistic insights for each strategy, offering a thorough and concise overview of recent advancements from 2014 to 2024.1 Introduction2 Methanol Activation Strategies3 Hydrogenation of Carbonyls4 Methylation of Carbonyls5 Outlook and Summary
Keywords: methanol; hydrogenation; dehydrogenation; methylation; aldehyde; ketone; chalcone; carbonyl